Antigen presentation by Ia+ B cell hybridomas to H-2-restricted T cell hybridomas. - Kappler, J (1982)
The Ia+, H-2d BALB/c lymphoma cell line L10.A 2J was fused to T cell-depleted spleen cells from mouse strains bearing other H-2 haplotypes. A portion of the selected hybrids expressed Ia antigens of the normal spleen cell partner in the fusion as evidenced by their presentation of various antigens to a set of antigen-specific I-region-restricted T cell hybridomas. Three cloned hybrids were studied in detail. Antigen presentation was shown to be inhibited specifically by monoclonal anti-Ia antibodies. Both I-A and I-E molecules were expressed, including in the one case examined hybrid I-A and I-E molecules between the H-2d and H-2b haplotypes. These Ia+ B cell hybridomas provide a useful set of tools for studying the role of I-region-encoded molecules in antigen presentation to T cells.